A potential dermal substitute using decellularized dermis extracellular matrix derived bio-ink - Joo-Yun Won; Mi-Hee Lee; Mi-Jeong Kim; Kyung-Hyun Min; Geunseon Ahn; Ji-Seok Han; Songwan Jin; Won-Soo Yun; Jin-Hyung Shim (Artificial Cells, Nanomedicine, and Biotechnology)
Upon bioprinting, cells are mixed with a biomaterial to fabricate a living tissue, thus emphasizing the importance of biomaterials. The biomaterial used in this study was a bio-ink prepared using skin decellularized extracellular matrix (dECM). Skin dECM was extracted by treating the dermis with chemicals and enzymes; the basic structural and functional proteins of the ECM, including collagen, glycosaminoglycans (GAGs), bioreactive materials and growth factors, were preserved, whereas the resident cells that might cause immune rejection or inflammatory responses were removed. The bio-ink based on dECM powder, together with human dermal fibroblasts (HDFs), was loaded into the nozzle of the 3D bioprinter to create the 3D construct. This construct underwent gelation with changing temperature while its shape was maintained for 7 days. The cells showed over 90% viability and proliferation. By analysing the gene expression pattern in the cells of the construct, the skin regenerative mechanism of the bio-ink was verified. Microarray results confirmed that the gene expression related to skin morphology and development had been enhanced because the bioreactive molecules and growth factors, in addition to residual ECM in dECM, provided an optimal condition for the HDFs.